Development of a Microsoft Excel-Based Management System for Secondary School Chemistry Laboratories - Puan Purnama Wati; Ibnu Khaldun; Sri Winarni; Muhammad Nazar; Zulfadli Zulfadli; Putri Nabilah (Jurnal Pemberdayaan Masyarakat, 2025)
Inefficient digital systems for managing chemistry laboratories in secondary schools often impede effective record-keeping, inventory management, and practicum reporting. This study developed Chemlab Excel, a practical and accessible offline Microsoft Excel-based laboratory management system, eliminating the need for an internet connection or additional software. Employing a Research and Development (RD) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), and involved nine purposively selected respondents, including chemistry teachers, laboratory heads, and lab assistants from SMA Negeri 1 Bireuen and SMA Negeri 1 Samalanga. The study utilized expert validation sheets, teacher response questionnaires, and the System Usability Scale (SUS) for data collection. Validity was assessed using Aiken's V, and inter-rater reliability was measured via the Intraclass Correlation Coefficient (ICC). Three experts validated the system, with trials conducted in two secondary schools in Bireuen Regency. Results showed high feasibility, with Aiken's V coefficients of 0.852 (media) and 0.869 (material), and ICC values of 0.768 (media) and 0.761 (material), indicating good reliability. The SUS score averaged 72.22%, and teacher responses reached 94.64%, reflecting user-friendliness and enhanced efficiency. Chemlab Excel proves to be a feasible, contextually relevant solution for laboratory management, contributing to streamlined administrative processes in science education and offering a scalable, accessible tool for secondary schools.